2018
DOI: 10.1103/physrevb.98.100503
|View full text |Cite
|
Sign up to set email alerts
|

Normal-state properties of the antiperovskite oxide Sr3xSnO revealed by Sn119 -NMR

Abstract: We have performed 119 Sn-NMR measurements on the antiperovskite oxide superconductor Sr 3−x SnO to investigate how its normal state changes with the Sr deficiency. A two-peak structure was observed in the NMR spectra of all the measured samples. This suggests that the phase separation tends to occur between the nearly stoichiometric and heavily Sr-deficient Sr 3−x SnO phases. The measurement of the nuclear spin-lattice relaxation rate 1/T 1 indicates that the Sr-deficient phase shows a conventional metallic be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
4
12
0
Order By: Relevance
“…The present results confirm the Sn 4state and thus the validity of the band structure calculations. In this sense, these results are consistent with the NMR experiments observing the 1/T 1 attributable to the Dirac dispersion [15]. Furthermore, since the large amount of the Sr deficiency to "Sr 3 Sn 2 O 2 " or "Sr 2 Sn 2 O 2 " leads to heavy hole doping, the deficient phase with a large portion of such Sn sites with neighboring Sr deficiency would exhibit metallic 1/T 1 , as indeed observed in the NMR measurements.…”
Section: Comparison With Nmrsupporting
confidence: 91%
See 4 more Smart Citations
“…The present results confirm the Sn 4state and thus the validity of the band structure calculations. In this sense, these results are consistent with the NMR experiments observing the 1/T 1 attributable to the Dirac dispersion [15]. Furthermore, since the large amount of the Sr deficiency to "Sr 3 Sn 2 O 2 " or "Sr 2 Sn 2 O 2 " leads to heavy hole doping, the deficient phase with a large portion of such Sn sites with neighboring Sr deficiency would exhibit metallic 1/T 1 , as indeed observed in the NMR measurements.…”
Section: Comparison With Nmrsupporting
confidence: 91%
“…We comment that the phase splitting into the nearly stoichiometric and deficient compounds has been suggested in the previous study of magnetization [16] and indeed observed with NMR [15]. Since NMR probes properties of the conduction electrons though it measures the Zeeman energy of the Sn nucleus, the splitting in the NMR spectrum suggests that one sample consists of two materials ("phases") with distinct stoichiometries as shown in Fig.…”
Section: Comparison With Nmrsupporting
confidence: 68%
See 3 more Smart Citations